Population age structure, saving, capital flows and the real exchange rate: A survey of the literature - Hassan, Kamrul; Salim, Ruhul; Bloch, Harry (Wiley-Blackwell Publishing Ltd., 2011)
This paper surveys the existing literature on the effects of population age structure on saving, capital flows and the real exchange rate. We build on previous surveys of age structure and saving behaviour by including extensive discussion of international linkages, specifically the impact on capital flows and real exchange rates. We also point to unresolved issues that need to be addressed given that population aging has serious policy implications in the developed economies these days.